Flavonoid silybin improves the response to radiotherapy in invasive bladder cancer - Prack Mc Cormick, Bárbara Patricia (2018)
Conservative treatment for invasive bladder cancer (BC) involves a complete transurethral tumor resection combined with chemotherapy (CT) and radiotherapy (RT). The major obstacles of chemo-radiotherapy are the addition of the toxicities of RT and CT, and the recurrence due to RT and CT resistances. The flavonoid Silybin (Sb) inhibits pathways involved in cell survival and resistance mechanisms, therefore the purpose of this paper was to study in vitro and in vivo, the ability of Sb to improve the response to RT, in two murine BC cell lines, with different levels of invasiveness, placing emphasis on radio-sensitivity, and pathways involved in radio-resistance and survival. In vitro, Sb radio-sensitized murine invasive cells through the inhibition of RT-induced NF-κB and PI3K pathways, and the increase of oxidative stress, while non-invasive cells did not show to be sensitized. In vivo, Sb improved RT-response and overall survival in invasive murine tumors. As Sb is already being tested in clinical trials for other urological cancers and it improves RT-response in invasive BC, these results could have translational relevance, supporting further research.